Factors Influencing the Implementation of Cooperative Learning: Elementary School Teacher Education Department Students’ Perspectives - Wijaya Heru Santosa; Anselmus Sudirman (research, training and philanthropy institution Natural Aceh, 2023)
Several factors influence the administration of cooperative learning courses, including the learning model, collaboration, social behavior and attitude, and heterogeneity. This study aims to identify the factors that assist or impede the implementation of cooperative learning courses in two Elementary School Teacher Education Departments (PGSD) involving 40 students. The researchers used an approach known as purposeful sampling, in which they selected the sample by identifying particular features that were consistent with their research objectives and were expected to be able to provide solutions to research problems. This research was conducted at two private universities in Yogyakarta, Indonesia. A qualitative descriptive questionnaire was used to collect information on the supporting and inhibiting variables of cooperative learning. Grades in Indonesian language classes have been correlated with a group effort in completing assignments (78.75%). A contributing component, the students' propensity for cooperative learning in the academic appreciation course (78%), emerges subsequently. Another aspect is the desire to complete the assignment (77.25%). Furthermore, factors that encourage cooperative learning are investigated. More suitable media facilities are essential (75%), given that the brilliant students predominate (80.75%) but familiarize themselves with cooperative learning. These facts imply that cooperative learning lays the foundation for academy students' participation, engagement, and problem-solving to be implemented during the learning and teaching processes.